Stocking density of Nile tilapia in cages placed in a hydroelectric reservoir - Garcia, Fabiana; Romera, Daiane M.; Gozi, Kátia S.; Onaka, Eduardo M.; Fonseca, Fernando S.; Schalch, Sérgio H.C.; Candeira, Pedro G.; Guerra, Luis O.M. [UNESP]; Carmo, Fernando J.; Carneiro, Dalton J. [UNESP]; Martins, Maria Inez E.G. [UNESP]; Portella, Maria Célia [UNESP] (Elsevier, 2013)
The Brazilian government has been encouraging fish farming in cages in federal water bodies, including hydroelectric reservoirs. Despite the government support, it is a new activity and the production model still needs some adjustment to reduce the production costs and achieve sustainability. The aims of this study were to determine the appropriate stocking density of Nile tilapia in cages in a hydroelectric reservoir and to evaluate to what extent fish size selection could improve their uniformity. Twelve cages (6m3) were placed at the Fish Farmers' Cooperative of Santa Fé do Sul and Region, Ilha Solteira reservoir, São Paulo, Brazil (20°12'10″S, 50°58'31.15″W). In stage I (initial fish weight, 78g), four stocking densities were tested: D1-800, D2-2000, D3-2500 and D4-3000 fish/cage, with three replicates. At the end of this stage (average fish weight, 255g), the fish were selected into three sizes, except for D1. In stage II, four stocking densities were tested, designed to obtain the following final production: D1-100kg/m3 (800 non-selected fish/cage), D2-80kg/m3 (600 fish/cage), D3-100kg/m3 (800 fish/cage) and D4-120kg/m3 (900 fish/cage). The trial ended when the fish weighed 800g. By reducing the initial stocking density from 2500 to 800 tilapia juveniles per cage, there was no need for selection. The growth performance was higher, the feed conversion rate was better and the time taken to reach harvesting was shorter. Consequently, the production cost reduced and the operating profit increased. Using the lowest initial stocking density, the risk of disease outbreak was also lower, and there was no need to use drugs for disease control since the mortality rate and occurrences of disease and deformity decreased and the dissolved oxygen level inside the cages was higher. © 2013 Elsevier B.V.
Keywords: Oreochromis niloticus; Pathology; Performance; Production cost; Water quality